Cerebral O2 and CO2 transport in isovolumic haemodilution: Compensation of cerebral delivery of O2 and maintenance of cerebrovascular reactivity to CO2. Issue 1 (January 2023) - Carr, Jay MJR; Ainslie, Philip N; MacLeod, David B; Tremblay, Joshua C; Nowak-Flück, Daniela; Howe, Connor A; Stembridge, Mike; Patrician, Alexander; Coombs, Geoff B; Stacey, Benjamin S; Bailey, Damian M; Green, Daniel J; et al.
This study investigated the influence of acute reductions in arterial O2 content (CaO2 ) via isovolumic haemodilution on global cerebral blood flow (gCBF) and cerebrovascular CO2 reactivity (CVR) in 11 healthy males (age; 28 ± 7 years: body mass index; 23 ± 2 kg/m 2 ). Radial artery and internal jugular vein catheters provided measurement of blood pressure and gases, quantification of cerebral metabolism, cerebral CO2 washout, and trans-cerebral nitrite exchange (ozone based chemiluminescence). Prior to and following haemodilution, the partial pressure of arterial CO2 (PaCO2 ) was elevated with dynamic end-tidal forcing while gCBF was measured with duplex ultrasound. CVR was determined as the slope of the gCBF response and PaCO2 . Replacement of ∼20% of blood volume with an equal volume of 5% human serum albumin (Alburex® 5%) reduced haemoglobin (13.8 ± 0.8 vs. 11.3 ± 0.6 g/dL; P < 0.001) and CaO2 (18.9 ± 1.0 vs 15.0 ± 0.8 mL/dL P < 0.001), elevated gCBF (+18 ± 11%; P = 0.002), preserved cerebral oxygen delivery (P = 0.49), and elevated CO2 washout (+11%; P = 0.01). The net cerebral uptake of nitrite (11.6 ± 14.0 nmol/min; P = 0.027) at baseline was abolished following haemodilution (−3.6 ± 17.9 nmol/min; P = 0.54), perhaps underpinning the conservation of CVR (61.7 ± 19.0 vs. 69.0 ± 19.2 mL/min/mmHg; P = 0.23). These findings demonstrate that the cerebrovascular responses to acute anaemia in healthy humans are sufficient to support the maintenance of CVR.